Comparison of multicarrier PWM techniques for nine- level inverter drive an open-end winding induction motor - Abbas, Ali K. Abdul (Basrah Journal for Engineering Sciences, 2017)
Different modulation techniques of Nine-Level Inverter (NLI) for an Open-End Winding Induction Motor (OEWIM) is presented in this paper. The two five-level inverters are fed by both ends of open-winding induction motor. The five-level inverters are connected by cascading of four two-level inverters. This inverter topology does not neutral-point fluctuation so this topology different from neutral-point clamping inverter and this scheme does not the diode clamping to fixed neutral point. In the different multilevel sinusoidal pulse width modulations used for the proposed topology. The drive is implemented and simulation with an open-end winding induction motor and simulation results are presented.